EVALUASI KEBIJAKAN PENANGGULANGAN STUNTING DI KABUPATEN LOMBOK TIMUR - KABUL, LALU MUH. (Universitas Mahasaraswati K. Mataram, 2024)
The scope of the study is process evaluation and outcome evaluation. The aim of the study is to analysis an evaluation process and outcome evalution. The study method used is mixed methods, namely quantitative and qualitative. The result of study showed that implementation process of stunting intervention at locus village include 8 integrated actions where each action has been fully achieved target 100 percent. Stunting intervention at locus village significantly influence to the outcome namely decreasing of stunting prevalency. In addition, there is very strong negative correlation between amount of locus village and stunting prevalency